Analisis Representasi Aspek Sustainable Development Goals (SDGs) pada Buku Teks IPA SMP di Kota Medan - Dini Indah Syahfitri; Ummi Nur Afinni Dwi Jayanti (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to examine how the Sustainable Development Goals (SDGs) are presented in science textbooks used by seventh-grade junior high school students in Medan. The method employed was content analysis of two science textbooks published by the Ministry of Education and Yudhistira. The study focused on six SDG targets: Goals 2, 3, 6, 13, 14, and 15. The results show that the presentation of SDGs in the textbooks varies in clarity, quantity, quality, and context. Environmental aspects (SDGs 13, 14, and 15) appear more frequently than social and economic aspects (SDGs 2, 3, and 6), which tend to appear indirectly. Overall, the integration of SDGs in the textbooks does not fully reflect the principles of Education for Sustainable Development (ESD), as the content primarily emphasizes cognitive components rather than practical skills, attitudes, and actions. These findings  highlight  the importance  of  science textbooks in supporting sustainable education through curriculum updates, enhancement of ESD competencies, and the development of evaluation systems aligned with SDG achievement. Keywords: Content analysis, Sustainable Development Goals (SDGs) aspects, Science textbooks